Blue Shadows Farm : a novel - Apps, Jerold W., 1934- (Terrace Books, 2009)
"Silas Starkweather, a Civil War veteran, is drawn to Wisconsin and homesteads 160 acres in Ames County, where he is known as the mysterious farmer forever digging holes. After years of hardship and toil, however, Silas develops a commitment to farming his land and respect for his new community. When Silas's son Abe inherits Blue Shadows Farm he chooses to keep the land out of reluctant necessity, distilling and distributing "purified corn water" throughout Prohibition and the Great Depression in order to stay solvent. Abe's daughter, Emma, willingly takes over the farm after her mother's death. Emma's love for this place inspires her to open the farm to school-children and families who share her respect for it. As she considers selling the land, Emma is confronted with a difficult question - who, through thick and thin, will care for Blue Shadows Farm as her family has done for over a century?